Volatile organic compounds in naturally fermented milk and milk fermented using yeasts, lactic acid bacteria and their combinations as starter cultures - Gadaga, Henry Tendekayi (Array, 2007)
The volatile organic compounds present in 18 Zimbabwean naturally fermented milk (amasi) samples and those produced by various yeasts, lactic acid bacteria (LAB) and yeast/ LAB combinations were determined using headspace gas chromatography. The yeast strains used were: Candida kefyr 23, C. lipolytica 57, Saccharomyces cerevisiae 71, C. lusitaniae 68, C. tropicalis 78, C. lusitaniae 63, C. colliculosa 41, S. dairenensis 32, and Dekkera bruxellensis 43, and were coded Y1 to Y9, respectively. The LAB strains used were Lactococcus lactis subsp. lactis Lc39, L. lactis subsp. lactis Lc261, Lactobacillus paracasei Lb11, and L. lactis subsp. lactis biovar. diacetylactis C1, and were coded B1 to B4, respectively. Some of the volatile organic compounds found in amasi were acetaldehyde, ethanol, acetone, 2-methyl propanal, 2-methyl-1-propanol and 3-methyl-1-butanol. However, the levels of volatile organic compounds in the naturally fermented milk (NFM) samples varied from one sample to another, with acetaldehyde ranging from 0.1–18.4 ppm, 3-methyl butanal from <0.1–0.47 ppm and ethanol from 39.3–656 ppm. The LAB/C. kefyr 23 (B/Y1) co-cultures produced significantly (p<0.05) higher levels of acetaldehyde and ethanol than the levels found in the NFM